The suburban crisis: white America and the war on drugs - Lassiter, Matthew D. (Princeton University Press, 2023)
"Most accounts of post-1950s political history tell the story of of the war on drugs as part of a racial system of social control of urban minority populations, an extension of the federal war on black street crime and the foundation for the "new Jim Crow" of mass incarceration as key characteristics of the U.S. in this period. But as the Nixon White House understood, and as the Carter and Reagan administrations also learned, there were not nearly enough urban heroin addicts in America to sustain a national war on drugs. This book argues that the long war on drugs has reflected both the bipartisan mandate for urban crime control and the balancing act required to resolve an impossible public policy: the criminalization of the social practices and consumer choices of tens of millions of white middle-class Americans constantly categorized as "otherwise law-abiding citizens."" That is, the white middle class was just as much a target as minority populations. The criminalization of marijuana - the white middleclass drug problem - moved to the epicenter of the national war on drugs during the Nixon era. White middle-class youth by the millions were both the primary victims of the organized drug trade and excessive drug war enforcement, but policymakers also remained committed to deterring their illegal drug use, controlling their subculture, and coercing them into rehabilitation through criminal law. Only with the emergence of crack cocaine epidemic of the mid-1980s did this use of state power move out of suburbs and remgaged more dramatically in urban and minority areas. This book tells a history of how state institutions, mass media, and grassroots political movements long constructed the wars on drugs, crime, and delinquency through the lens of suburban crisis while repeatedly launching bipartisan/nonpartisan crusades to protect white middle-class victims from perceived and actual threats, both internal and external. The book works on a national, regional, and local level, with deep case studies of major areas like San Francisco, LA, Washington, and New York. This history uses the lens of the suburban drug war to examine the consequences when affluent white suburban families serve as the nation's heroes and victims all at the same time, in politics, policy, and popular culture"--